SAT0140 Hypersomnolence in fibromyalgia syndrome. (1st June 2001) - Rizzi, M; Sarzi-Puttini, P; Andreoli, A; Panni, B; Pecis, M; Vassallo, FG; Carrabba, M; Sergi, M
Abstract : Background: Objectives: To evaluate hypersomnolence in patients affected by fibromyalgia syndrome. Methods: Thirty consecutive patients affected by fibromyalgia syndrome (FMS) (28 F) underwent a general sleep questionnaire, the Epsworth sleepiness scale (ESS), formal polysomnography, and lung function tests. Results: Patients complaining of daytime hypersomnolence had a higher number of tender points (15 ± 2 vs 12 ± 1, p < 0.01), a greater score of subjective pain (72 ± 15 vs 52 ± 13, p = 0.05) and more fatigue (p = 0.04), about twice as many arousals per hour and a lower sleep efficiency than patients who did not report this symptom. TLco was more impaired and the occurrence of PB higher. FMS patients who referred daytime somnolence slept significantly less efficiently than the FMS with no day time somnolence (p < 0.05), had a lower proportion of stage 3 sleep (5 ± 2% vs 12 ± 3%; p < 0.001), stage 4 (1 ± 0.5% vs 4 ± 1%; p < 0.001), and twice as many arousals per hour of sleep (p < 0.01). The respiratory pattern of FMS patients with hypersomnolence showed a higher occurrence of periodic breathing (p = 0.02). The short length of apneas and hypopneas did not affect the apnea/hypopnea index (5.1 ± 3 vs 7 ± 4; p = ns), but FMS patients with daytime hypersomnolence had a greater number of desaturations per hour of sleep (11 ± 6 vs 6 ± 5; p < 0.05). Pulmonary volumes did not differ between the two groups. Conclusion: The occurrence of daytime hypersomnolence in FMS patients, is linked to a greater severity of fibromyalgia symptoms and to a more severe polisomnographic alterations.